Canadian Expert Panel Recommendations on the Management of CNS Symptoms Related to Efavirenz - M John Gill; Anita Rachlis; Sharon Walmsley; Mark Halman; The Efavirenz Consensus Working Group (Canadian Journal of Infectious Diseases)
Efavirenz is a potent antiretroviral agent used in combination with other antiretroviral agents as part of highly active antiretroviral therapy. Efavirenz is generally well tolerated because the majority of its adverse effects are self-limiting, with central nervous symptoms and rash being the most frequent. In routine practice, the discontinuation rate of efavirenz due to adverse effects appears higher than that described in clinical trials. To minimize early treatment interruption and maximize the benefit of long term viral suppression that can be achieved with efavirenz therapy, health care providers and patients have identified that there is a need for information, education about and practical tools for the management of efavirenz-related side effects. To this end, a panel of experts in the care of HIV patients consisting of primary care physicians, infectious disease specialists, psychiatrists and pharmacists was convened. Through the evaluation of current literature and discussion among the group, the panel arrived at consensus recommendations. The present report outlines general management recommendations that apply to adverse effects related to efavirenz initiation, as well as specific management strategies for central nervous system symptoms such as agitation, sleep disturbances, dreams, dizziness, impaired concentration and depression. It is hoped that these practical recommendations will aid clinicians in minimizing and improving patient tolerance of side effects, thereby achieving improved adherence and patient outcomes.